The Good Life An Introduction to Ethics - Pleger, Wolfgang (Stuttgart : J.B. Metzler : Imprint: Palgrave Macmillan, 2023)
The book offers a historical-systematic overview of the most important concepts of ethics. From antiquity to modern times, from Plato to Habermas, each concept is represented by three to four historically significant positions of important thinkers. Central quotations allow textual access to the respective position, which is explained compactly and vividly. With the title "The Good Life" the author points to the anthropological basis of all ethics. The book is interdisciplinary in nature, incorporating philosophical approaches as well as those from the fields of theology, biology, psychology, sociology, and politics. For the 2nd edition, the book has been expanded to include chapters on pedagogical ethics as well as universal human rights. The translation was done with the help of artificial intelligence. The author (with the support of Barbara Pleger) has subsequently revised the text further in an endeavour to refine the work stylistically.
I. Ancient ethics of happiness -- II. Faith and reason: Philosophical-theological ethics -- III. Moral feeling - Ethics and metaethics -- IV. Practical reason - The ethics of duty -- V. Happiness and utility - Utilitarianism -- VI. Ethics of values -- VII. The development of morality - Genetic concepts of ethics -- VIII. Education and formation - Pedagogical ethics -- IX. Concepts of radical moral criticism -- X. Between ideology and reason - on political ethics -- XI. Responsibility and discourse ethics -- XII. Ethics and universal human rights.
Keywords: Ethics; Moral Philosophy and Applied Ethics